A direct resistance heating method for shaped blank. (February 2021) - Demazel, N.; Laurent, H.; Carin, M.; Le Masson, P.; Salmon-Legagneur, H.
Abstract: Direct electric resistance heating allows fast and uniform heating of rectangular blanks in hot forming process. To adapt this technology for any blank shape, a solution is proposed by splitting the part in several rectangular strips heated by electric generators. By optimizing the number, the orientation and the dimensions of rectangular strips to reduce added material and energy costs, this method is applied in the case of a windscreen upright blank. From a 3D thermoelectric model taking into account the imperfection of contact between the blank and the electrodes, integrating a PID-controller and the electrical power limitations, a heating demonstrator of this part is developed. This heating method has proved to be effective in heating shaped blanks quickly and uniformly during the hot stamping process.